Effect of laser incidence angle on cut quality of 4 mm thick stainless steel sheet using fiber laser. (July 2016) - Mullick, Suvradip; Agrawal, Arpit Kumar; Nath, Ashish Kumar
Abstract: Fiber laser has potential to outperform the more traditionally used CO2 lasers in sheet metal cutting applications due to its higher efficiency, better beam quality, reliability and ease of beam delivery through optical fiber. It has been however, reported that the higher focusability and shorter wavelength are advantageous for cutting thin metal sheets up to about 2 mm only. Better focasability results in narrower kerf-width, which leads to an earlier flow separation in the flow of assist gas within the kerf, resulting in uncontrolled material removal and poor cut quality. However, the advarse effect of tight focusability can be taken care by shifting the focal point position towards the bottom surface of work-piece, which results in a wider kerf size. This results in a more stable flow within the kerf for a longer depth, which improves the cut quality. It has also been reported that fiber laser has an unfavourable angle of incidence during cutting of thick sections, resulting in poor absorption at the metal surface. Therefore, the effect of laser incidence angle, along with other process parameters, viz. cutting speed and assist gas pressure on the cut quality of 4 mm thick steel sheet has been investigated. The change in laser incidence angle has been incorporated by inclining the beam towards and away from the cut front, and the quality factors are taken as the ratio of kerf width and the striation depth. Besides the absorption of laser radiation, beam inclination is also expected to influence the gas flow characteristics inside the kerf, shear force phenomena on the molten pool, laser beam coupling and laser power distribution at the inclined cut surface. Design of experiment has been used by implementing response surface methodology (RSM) to study the parametric dependence of cut quality, as well as to find out the optimum cut quality. An improvement in quality has been observed for both the inclination due to the combined effect of multiple phenomena. Highlights: Effect of laser incidence angle on cut quality has been studied. Study was done with incidence angle changed away and towards the cut front. Beam tilted away from normal to top surface was found to improve cut quality. Cut quality has been optimized using response surface methodology.